Analisis Efisiesni Blower Mesin Pengering Padi dengan Daya Penggerak 1000 RPM dan 818 RPM di CV Jasa Bhakti Karawang - Rudi Handoko; Kardiman Kardiman; Deri Teguh Santoso (Peneliti.net, 2022)
Along with the times, the need for technology is increasingly needed to support increasing human needs, including in the agricultural sector, where a tool is needed to dry rice quickly after going through the harvest process, therefore a Blower Machine for Drying Rice is made. The blower used in the rice drying process is a centrifugal type with a curved blade, the workings of this blower machine is to pour rice into a room with an area of ​​5 x 12 m which has been installed in a series equipped with a screen that has a height of 60 cm from the ground, and a width of 60 cm. screen maximum of 2.5 mm, redistribute the grain so that it looks evenly distributed with a maximum pile height of 50 cm, then turn on the combustion furnace with gas fuel so that the temperature reaches 135℃, then turn on the driving motor, and wait until the water content in the rice reaches 13.8 -14%. Because according to the Indonesian National Standard (SNI) for milled dry grain, the recommended moisture content is 14%. From the analysis results, it is found that the blower is able to provide heat of 44.4 for 1000 Rpm blower rotation, and 40.2 for 818 Rpm.